Case of complete response to neoadjuvant therapy using nivolumab in a patient with metastatic renal cell carcinoma. (25th April 2018) - Ikarashi, Daiki; Kato, Yoichiro; Katagiri, Hirokatsu; Takahara, Takeshi; Uesugi, Noriyuki; Shiomi, Ei; Sugimura, Jun; Nitta, Hiroyuki; Sugai, Tamotsu; Obara, Wataru
Abstract: Here, we report a case of a 68‐year‐old woman with cT4N0M1 (liver invasion and multiple lung metastases) metastatic renal cell carcinoma. We could carry out less invasive nephrectomy with partial hepatectomy because nivolumab administration as second‐line therapy reduced the primary tumor remarkably. To the best of our knowledge, this is the first report of the use of nivolumab before carrying out surgery, and histological findings showed a pathological complete response.